The emotional well-being of journalists exposed to traumatic events: A mapping review. (December 2021) - Osmann, Jonas; Dvorkin, Jeffrey; Inbar, Yoel; Page-Gould, Elizabeth; Feinstein, Anthony
This article presents a mapping review of the available literature on the emotional well-being of journalists exposed to traumatic events. The review consists of three parts: (a) a summary of the results of trauma-related literature; (b) identification of the limitations of studies to date; and (c) suggestions for future research. The overview of the reviewed studies is provided as a table.